J07 Early morning bright light therapy: its next-day effects on early morning physical performance, temperature, and mood - Calcagni, Ed; Hajdukiewicz, Dani; Blow, Liv; Durkin, Kyle; Porritt, George (Graduate Journal of Sports Science, Coaching, Management, & Rehabilitation, 2024)
Many different popular sports such as swimming, rowing or team-based sports involve having to perform whether in training or competition at a high level in the early morning (Olympics.com, 2023). Various research papers in the past have shown that there is a distinct diurnal variation in physical performance. Finding ways to improve early morning performance would greatly benefit many athletes and teams in multiple disciplines. 11 active males [mean ± SD: age, 21 ± 1 years, body mass, 78 ± 8 kg and stature, 180 ± 5 cm) volunteered, completed two familiarisations. Then two experimental sessions randomly allocated in a counterbalanced order 1) bright light therapy/ 2) no bright light therapy was administered at 07:00 h for 1 h the next morning (07:00 h) participants came into the laboratory where Intra-aural temperature, mood was assessed using the Perceived Onset Mood State questionnaire and right and left grip strength using a hand grip dynamometer were taken. Finally, participants undertook a warmup, the completed 10 × 20 m repeated sprints (RS) with 30 s recoveries on an indoor running track, with heart rate, finishing time and perceived exertion measured every sprint. Blood lactate was measured at rest, after the warm-up and post RS. Data were analysed using general-linear models.